x phần -5 = 6 phần -10
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\dfrac{1}{2}-\dfrac{2}{5}\right)+\left(-1\dfrac{1}{3}-\dfrac{5}{6}\right)-\left(-x+\dfrac{1}{10}\right)=\dfrac{3}{10}\)
\(\left(\dfrac{5}{10}-\dfrac{4}{10}\right)+\left(\dfrac{-2}{3}-\dfrac{5}{6}\right)+x-\dfrac{1}{10}=\dfrac{3}{10}\)
\(\dfrac{1}{10}+\left(\dfrac{-4}{6}-\dfrac{5}{6}\right)+x=\dfrac{3}{10}+\dfrac{1}{10}\)
\(\dfrac{1}{10}+\dfrac{-3}{2}+x=\dfrac{4}{10}\)
\(\dfrac{-3}{2}+x=\dfrac{4}{10}-\dfrac{1}{10}\)
\(\dfrac{-3}{2}+x=\dfrac{3}{10}\)
\(x=\dfrac{3}{10}-\dfrac{-3}{2}\)
\(x=\dfrac{3}{10}-\dfrac{-15}{10}\)
\(x=\dfrac{18}{10}=\dfrac{9}{5}\)
2:
a: =>x-1/5=2/15
=>x=2/15+3/15=5/15=1/3
b: =>x+7/12=-5/6-2/6=-7/6
=>x=-14/12-7/12=-21/12=-7/4
c: =>x+2/3=-10/3
=>x=-4
d: =>1/4:x=-11/4
=>x=-1/4:11/4=-1/11
e: =>8:x=1,6
=>x=5
\(a,\dfrac{6}{5}=\dfrac{18}{x}\\ \Rightarrow x=18:\dfrac{6}{5}\\ \Rightarrow x=15\\ b,\dfrac{3}{4}=\dfrac{-21}{x}\\ \Rightarrow x=-21:\dfrac{3}{4}\\ \Rightarrow x=-28\\ c,\dfrac{2}{-7}=\dfrac{18}{x}\\ \Rightarrow x=18:\dfrac{2}{-7}\\ \Rightarrow x=-63\\ d,\dfrac{-5}{2}=\dfrac{10}{-x}\\ \Rightarrow x=-10:\dfrac{-5}{2}\\ \Rightarrow x=4\)
\(a,\dfrac{6}{5}=\dfrac{18}{x}\Rightarrow6.x=5.18=90\\ \Rightarrow6.x=90\\ \Rightarrow x=15\\ b,\dfrac{3}{4}=\dfrac{-21}{x}\Rightarrow3.x=4.21=84\\ \Rightarrow x=28\)
Bài giải
\(\frac{2}{3}+\frac{3}{4}+\frac{4}{5}=\frac{40}{60}+\frac{45}{60}+\frac{48}{60}=\frac{133}{60}\)
\(\frac{8}{5}+\frac{7}{6}+\frac{10}{9}+\frac{1}{2}=\frac{144}{90}+\frac{105}{90}+\frac{100}{90}+\frac{45}{90}=\frac{394}{90}\)
\(\frac{15}{17}-\frac{11}{13}+\frac{3}{26}=\frac{390}{442}+\frac{374}{442}+\frac{51}{442}=\frac{815}{442}\)
\(\frac{9}{12}\text{ x }\frac{4}{3}\text{ : }\frac{8}{5}=\frac{9}{12}\text{ x }\frac{4}{3}\text{ x }\frac{5}{8}=\frac{9\text{ x }4\text{ x }5}{12\text{ x }3\text{ x }8}=\frac{5}{8}\)
\(\frac{4}{5}\text{ x }\frac{15}{8}\text{ : }\frac{5}{7}=\frac{4}{5}\text{ x }\frac{15}{8}\text{ x }\frac{7}{5}=\frac{4\text{ x }15\text{ x }7}{5\text{ x }8\text{ x }5}=\frac{21}{10}\)
\(\frac{2}{3}+\frac{3}{4}+\frac{4}{5}=\frac{40}{60}+\frac{45}{60}+\frac{48}{60}=\frac{133}{60}\)
\(\frac{8}{5}+\frac{7}{6}+\frac{10}{9}+\frac{1}{2}=\frac{144}{90}+\frac{105}{90}+\frac{100}{90}+\frac{45}{90}=\frac{197}{45}\)
\(\frac{15}{17}-\frac{11}{13}+\frac{1}{26}=\frac{390}{442}+\frac{374}{442}+\frac{51}{442}=\frac{815}{442}\)
\(\frac{9}{12}\times\frac{4}{3}:\frac{8}{5}=1:\frac{8}{5}=\frac{5}{8}\)
\(\frac{4}{5}\times\frac{15}{8}:\frac{5}{7}=\frac{3}{2}:\frac{5}{7}=\frac{21}{10}\)
Bài 1 :Bỏ dấu ngoặc
2007-(7-3+4)
= 2007 -7+3-4
= 1999
6+[(-5) + 4 - 1 ]
= 6-5+4-1
=4
5-[(-6+8-2]
= 5+6-8+2
=5
-10+(7-3+1)
= -10 +7-3+1
= -5
Bài 3 Tìm x
\(\dfrac{1}{3} = \dfrac{x}{6}\)
\(<=> x= \dfrac{1.6}{3}\)
\(<=> x=2\)
\(\dfrac{x}{-5}=\dfrac{6}{-10}\)
\(x\cdot\left(-10\right)=6\cdot\left(-5\right)\)
\(x\cdot\left(-10\right)=\left(-30\right)\)
\(x=\left(-30\right):\left(-10\right)\)
\(x=3\)
Vậy \(x=3\)
\(\Rightarrow\dfrac{3}{-5}=\dfrac{6}{-10}\)